Migration behavior for sockeye salmon adults of early race in the tributaries of Lake Nachikinskoye (western Kamchatka) - O. M. Zaporozhets; G. V. Zaporozhets (Известия ТИНРО)
Several stages are determined in the early run of sockeye salmon into tributaries of Lake Nachikinskoye: i) maturation of adults at depth, ii) concentration of adults in the mouths of the main tributaries, iii) entry of small flocks of the spawners into tributaries over a short distance, iv) upstream movement of lager flocks, v) thinning of flocks and formation of pairs, vi) spawning, and vii) death of spawned fish. In the large, stable accumulations formed in the mouths of tributaries, salmon choose paths for onward movement in the process of homing, by decoding imprinting information. There, aggregations of spawners are differentiated into separate flocks going to spawn on different spawning grounds. A peculiarity of this population of sockeye salmon is the retention of individuals not ready for spawning in many pits and catches of the rivers, with formation of well-visible compact schools, which dissipate as the fish mature. Filling of the spawning grounds in tributaries is determined by their characteristics, and typically occurs with a dome-shaped dynamics of intensity. The upward long-term trend in filling of the spawning grounds is observed in the lower Taburetka River (before its tributaries), while the downward trend — in the tributaries. Data on the filling for the last 5 years are presented. The greatest contribution to reproduction of the early sockeye salmon in Lake Nachikinskoye is provided by the lower reaches of the Taburetka River (41 %), whereas its tributary, the Verkhnyaya River, contributes 20 % and inputs of other tributaries are noticeably lower. In conditions of degradation for a part of the spawning grounds due to increased anthropogenic impact, all existing subpopulations should be preserved as productive as possible.